Time for a change: the ethics of student-led human subjects research on political violence. - Eck, Kristine; Cohen, Dara Kay (Third World Quarterly, 2021)
Undergraduate and master's students frequently conduct independent human subjects research on topics related to political violence and human rights – often, but not always, in the field. This work may involve the direct collection of data from vulnerable populations, in unstable contexts and about sensitive topics. However, despite the rich literature about research ethics, the ethics of advising, enabling and encouraging this type of student research on political violence has been largely overlooked. This article aims to (1) raise awareness about the proliferation of students engaging in human subject research on topics related to political violence and human rights; (2) discuss the risks inherent in this enterprise that are distinct from those that many faculty and doctoral students face; (3) provide suggestions about how to mitigate some of those risks, including a shift away from fieldwork-based research projects. We argue that it is a collective responsibility to require that students engage in ethical practices, including more thoughtful and creative selection of research questions, sites and populations.